Some Examples of Affine Isometries of Banach Spaces Arising from 1-D Dynamics - Navas-Flores, A (Elsevier GmbH, 2025)
We provide a large family of examples of affine isometries of the Banach spaces C0(S1), L1(S1) and L2(S1×S1) that are fixed-point-free despite being recurrent (in particular, they have zero drift). These come from natural cocycles on the group of circle diffeomorphisms, namely the logarithmic, affine and (a variation of the) Schwarzian derivative. Quite interestingly, they arise from diffeomorphisms that are generic in an appropriate context. We also show how to promote these examples in order to obtain families of commuting isometries satisfying the same properties. © 2025 Elsevier GmbH